Aspergillus fumigatus Influences Gasdermin-D-Dependent Pyroptosis of the Lung via Regulating Toll-Like Receptor 2-Mediated Regulatory T Cell Differentiation. (15th June 2021) - Yan, Wei; Zhao, Yi-si; Xie, Ke; Xing, Yu; Xu, Fang
Abstract : Purpose . Aspergillus fumigatus, as an opportunistic fungus, has developed a series of escape mechanisms under the host's immune response to obtain nutrients and promote fungal growth in the hostile environment. The immune escape of pathogens may be through suppressing the inflammatory response mediated by regulatory T cells (Tregs). The aim of this study was to explore whether A. fumigatus influences Gasdermin-D-dependent pyroptosis of the lung by regulating Toll-like receptor 2-mediated regulatory T cell differentiation. Methods . Collect peripheral blood from patients with A. fumigatus . ELISA kits we used to detect the expression levels of IL-1 β, IL-6, IL-2R, and IL-10 in the serum and flow cytometry to detect the percentage of CD4 + CD25 + Foxp3 + Tregs in the patients' peripheral blood mononuclear cells (PBMCs). The mouse model of A. fumigatus infection was constructed by tracheal instillation. The pathological changes in the lungs of the mice were observed under a microscope. The fungal load in the lung tissue was determined by the plate colony count. ELISA kit was used to detect the lung tissue homogenate proinflammatory cytokines TNF- α, IL-6, CCL2, and VEGF. Q-PCR was used for the detection of the expression of Foxp3 and TLR2 genes in the lung. Western blot was used for the detection of the expression of TLR2, Gasdermin-D (GSDMD), IL-1 α, and IL-1 β in the lung. Flow cytometry was used to detect splenic CD4 + CD25 + FOXP3 + Tregs. Using magnetic beads to extract CD4 + T cells from mice spleen, the effects of A. fumigatus conidia or TLR2 inhibitor (C29) to differentiate CD4 + T cells in vitro were tested. Results . The expression of Foxp3 and TLR2 in the lung tissue of mice infected with A. fumigatus increased, and we observed that the proportion of Tregs in both A. fumigatus infection patients and mice was upregulated. After using the CD25 neutralizing antibody, the number of Tregs in the mice spleen was significantly reduced. However, lung damage was reduced and the ability to clear lung fungi was enhanced. We found that the Tregs in TLR 2 − / − mice were significantly reduced and the nonlethal dose of A. fumigatus conidia did not cause severe lung damage in TLR 2 − / − mice. Compared with that of wild-type mice, the fungal burden in the lung of TLR2-deficient mice was reduced and the knockout of TLR2 changed the expression of GSDMD, IL-1 α, and IL-1 β in A. fumigatus . In in vitro experiments, we found that the inhibition of TLR2 can reduce Treg differentiation. Conclusions . A. fumigatus triggers CD4 + CD25 + FOXP3 + Treg proliferation and differentiation by activating the TLR2 pathway, which may be a potential mechanism for evading host defenses in A. fumigatus . This effect can modulate GSDMD-dependent pyroptosis and may partly involve TRL2 signaling.